The Digital Maturity Revealed: The Secret of Sustainable Transformation - Aliy, Muhammad Firyal; Younus, Muhammad; Lawelai, Herman (Jurnal Studi Pemerintahan, 2025)
Digital maturity represents an organization’s ability to adopt and integrate digital technologies into its operations, culture, and strategies. It plays a cru- cial role in navigating digital transformation while maintaining competitive- ness. This study explores how digital maturity serves as a key driver for effi- ciency, innovation, and sustainability. To understand research trends in this field, a bibliometric analysis was conducted covering studies from 2006 to 2024 using data from the Web of Science and Scopus databases. Analytical tools like R and Bibliometric were used to assess publication trends, citation patterns, and keyword co-occurrences. The findings revealed 852 publications on digital maturity, with a significant increase in research output between 2006 and 2023. Countries like Germany, Italy, and the UK emerged as the most active contributors, while Indonesia showed promising growth in this area. Many studies focused on sector-specific digital maturity models, particularly in Industry 4.0 and SMEs. Key research highlighted the importance of strategic alignment, leadership, and stakeholder engagement in achieving digital maturity. Digital maturity plays a pivotal role in driving transformation across various sectors. International collaborations have proven to enhance the impact of research, while sector-specific models help address unique challenges. However, the relationship between digital transformation and sustainability remains complex and requires further exploration. In conclusion, digital maturity is a foundation for transformative growth, enabling efficiency and sustainability. Future research should focus on developing context-specific models, particularly for developing countries, and fostering global collaboration to drive digital transformation forward.